Promoting Oral Health through Manager Training and Dental Referral at a Student-Run Homeless Shelter Clinic - Bui, Tu; Kindratt, Tiffany Billmeier; Reddy, Sumanth; Pagels, Patti (Journal of Student-Run Clinics, 2019)
Background: There is a need for oral health awareness among future clinicians and for dental services for homeless men. This quality improvement project aimed to: 1) improve oral health knowledge among physician assistant (PA), medical, and undergraduate student clinic managers; 2) determine the oral health needs of homeless men; and 3) establish a dental referral program for patients at a student-run free clinic. Methods: The project was conducted at a student-run free clinic embedded in a men’s homeless shelter in Dallas, Texas. Student managers underwent a training program that included a PowerPoint presentation and practice oral exams. Pre- and post-tests were used to assess their knowledge of different oral health topics. Patients of the clinic were surveyed for dental concerns at intake, and oral exams and referrals to a student-run dental clinic were done if indicated. Results: Student clinic managers (N=16) demonstrated improved knowledge on the recognition and treatment of some but not all dental conditions. Of the patients surveyed (N=13), most reported a history of dental caries (77%), had loose or missing teeth (62%), and brushed their teeth <2 times per day (69%). Although 65% of patients were referred to the dental clinic, only 9% went to their appointment. Conclusions: The manager training provided additional information and experience for clinic managers around oral health. The increased awareness made it easier for clinic managers to refer appropriate patients to the dental clinic. The newly implemented referral service provided a resource for the clinic to send patients that warrant higher level of dental care.